A Novel 3D Li/Li9Al4/Li‐Mg Alloy Anode for Superior Lithium Metal Batteries. (13th January 2023) - Li, Yijuan; Li, Junpeng; Xiao, Hong; Xie, Tangchao; Zheng, Weitao; He, Jialang; Zhu, Hengji; Huang, Shaoming
Abstract: Lithium metal has been recognized as the most promising anode material due to its high capacity and low electrode potential. However, the high reactivity, infinite volume variation, and uncontrolled dendrites growth of Li during long‐term cycling severely limit its practical applications. To address these issues, herein, a novel 3D Al/Mg/Li alloy (denoted as AM‐Li) anode is designed and constructed by a facile smelting‐rolling strategy, which improves the surface stability, electrochemical cycling stability, and rate capability in lithium metal batteries. Specifically, the optimized AM‐Li|AM‐Li symmetric cell exhibits low polarization voltage (< 20 mV) and perfect cycling stability at 1 mA cm −2 ‐1 mAh cm −2 for more than 1600 h. Moreover, the AM‐Li|NCM811 full cell exhibits superior rate capability up to 5 C and excellent cyclability for 100 cycles at 0.5 C with a high capacity retention of 90.8%. The realization of lithium‐poor or lithium‐free anode materials will be a major development trend of anode materials in the future. Therefore, the research shows that the construction of 3D alloy framework is beneficial to improve the cycling stability of Li anodes by suppressing the volume expansion effect and Li dendrite growth, which will promote the further development of lithium‐poor metal anodes. Abstract : A novel 3D Li/Li9 Al4 /Li‐Mg alloy anode is designed and fabricated by a facile alloy smelting‐rolling strategy, which improves the air sensitivity, structure stability, and Li plating/stripping behavior of lithium metal anode, and thus enhances the safety, electrochemical cycling stability, and rate capability in lithium metal batteries.